Protection of the Szachownica cave as an example of saving a valuable bat wintering shelter - Ignaczak, M.; Postawa, T. (Праці теріологічної школи, 2017)
The Szachownica cave (Kraków-Wieluń Upland, Poland) is one of the four largest wintering shelters for bats in Poland. Since the cessation of limestone mining, the number of wintering bats increased from 300 to more than 2,900 individuals. In recent years, there has been seen a gradual worsening of the cave structure due to frost destruction, which leads to the possible disintegration of a major part of the cave. To prevent damage of the cave the mining methods were used, because they can i) restrict access to the bats shelters, and ii) change microclimate. Monitoring of the abundance of bats was carried out twice during a winter: in end of January and in March. The temperature was measured in 3 points in the cave and in 1 outside. Securing the cave: i) only in minor degree changed the temperature amplitude, but not the mean temperature, whereas penetration of water (and also frost damage) was limited, ii) did not change either the species composition or species-specific long-term trends in the amount of bats hibernating in the cave. However, to assess fully the impact of changes, monitoring of both the bat fauna and microclimate will be continued during the next several years. Печера «Шаховниця» (Краківсько-Велюнська височина, Польща) є одним із чотирьох найбільших зимівельних сховищ кажанів у Польщі. Після припинення видобутку вапняку, кількість зимуючих тут кажанів зросла із 300 до понад 2900 особин. За останні роки спостерігається поступове погіршення структури печери через морози, що може призвести до обвалу значної її частини. Аби запобігти пошкодженню печери, було застосовано гірничі методи, що можуть 1) обмежити доступ кажанів до сховища та 2) змінити його мікроклімат. Моніторинг чисельності кажанів здійснено двічі за зиму: в кінці січня та у березні. Вимірювання температури проведено у трьох точках печери та в одній точці за її межами. Укріплення печери 1) незначно вплинуло на коливання температури, але не на її середній показник, обмежило проникнення води (а також морозне руйнування), і 2) не вплинуло на видовий склад або видоспецифічні довгострокові тенденції змін чисельності зимуючих в печері кажанів. Однак, для повної оцінки впливу змін, моніторинг хіроптерофауни та мікроклімату буде продовжуватися протягом наступних кілька років.